NicE-C efficiently reveals open chromatin–associated chromosome interactions at high resolution - Luo, Zhengyu; Zhang, Ran; Hu, Tengfei; Zhu, Yuting; Wu, Yueming; Li, Wenfei; Zhang, Zhi; Yao, Xuebiao; Liang, Haiyi; Song, Xiaoyuan (Genome Research, 2022)
Enhancer–promoter communication is known to regulate spatiotemporal dynamics of gene expression. Several methods are available to capture enhancer–promoter interactions, but they either require large amounts of starting materials and are costly, or provide a relative low resolution in chromatin contact maps. Here, we present nicking enzyme-assisted open chromatin interaction capture (NicE-C), a method that leverages nicking enzyme–mediated open chromatin profiling and chromosome conformation capture to enable robust and cost-effective detection of open chromatin interactions at high resolution, especially enhancer–promoter interactions. Using TNF stimulation and mouse kidney aging as models, we applied NicE-C to reveal characteristics of dynamic enhancer–promoter interactions.
10.1101/gr.275986.121